Evaluasi Hasil Persilangan Tanaman Padi Beras Hitam dengan Varietas Inpara 5 pada Lahan Terendam di Sumatera Selatan - Nabil, Shiva Naizak; Pratiwi, Shafira; Merlita Dewi, Ana Tasya; Fadhilah, Maratul; Ester Sitio, Rimma; Silalahi, Yose Armando; Hasmeda, Mery (Seminar Nasional Lahan Suboptimal, 2024)
Nabil, S. N., Pratiwi, S., Dewi, A. T. M., Fadhilah, M., Sitio, R. E., Silalahi, Y. A., & Hasmeda M. (2024). Evaluation of the hybridization results of black rice with inpara 5 varieties on waterlogged lands in South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 103–117). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Black rice had the disadvantages of high habitus, low productivity, and no soaking resistance. The purpose of this study was to determine the yield potential of black rice crosses with Inpara 5 varieties, especially on submerged land in South Sumatra. This field practice was carried out in South Sumatra Province. Field practice research on plant production was selected from the results of submerged stress tests, in testing plant growth and production the method used was Randomize Group Design (RDG). The results of research on submerged stress testing include the response of several black rice accessions to submerged stress, with measurements of parameters such as plant height, number of tillers, and chlorophyll levels before and after submersion for 14 days of submision. The results showed that plant height increased significantly from an average of 57.84 cm at 20 DAT (Days After Trasplatnting) to 83.93-96.00 cm at 49 DAT with accession I recording the highest height. The number of tillers decreased after submergence stress, with the highest average at 2.90 before submergence and the lowest at 1.29 at 49 DAT, while chlorophyll levels showed little change. In the final observation, accession H showed superior results in production parameters, such as number of panicles, total grain weight, and number of full grains, making it the most productive accession compared to others. In general, all accessions used in this study have the potential to be developed into new varieties of submergence-tolerant black rice. Based on the results of the study, it is suggested that better plant breeding can be done on black rice that shows the best resistance to submergence stress.